Broad plasma depletions detected in the bottomside of the equatorial F region: Simultaneous ROCSAT-1 and JULIA observations - Kil, Hyosub (2014)
We investigated the association of broad plasma depletions (BPDs) with plasma bubbles and ionospheric uplift in the equatorial F region using the coincident satellite and radar observations over Jicamarca in Peru. BPDs were detected by the first Republic of China satellite (ROCSAT-1) on the nights of 21 and 22 December 2002 during the period of moderate geomagnetic activity. The observations of the Jicamarca Unattended Long-term Investigations of the Ionosphere and Atmosphere radar and an ionosonde showed that the F peak height was lifted above the ROCSAT-1 altitude (600 km) at the times of the BPD detection. The fraction of NO+ was substantial at the locations of BPDs. These observations support the association of the BPDs with the ionospheric uplift. However, the absence of large backscatter plumes at the times of the BPD detection indicates that the BPDs were not produced by a single large bubble or a merger of bubbles.